Fuzzy Methodology for Frequency Response - Ferreira, Carlos Cesar Teixeira (2010)
Submitted by Aparecida Cruz (cidazen@gmail.com) on 2010-08-27T12:39:53Z No. of bitstreams: 1 ISIE2010_Final_Version.pdf: 122281 bytes, checksum: bbd943a54de73233f36a5b650f9aa516 (MD5)